What was the set of ubiquitin and ubiquitin-like conjugating enzymes in the eukaryote common ancestor? - Michelle, C.; Vourc'h, P.; Mignon, L.; Andres, C.R. (Journal of Molecular Evolution, 2009)
Ubiquitin (Ub)-conjugating enzymes (E2) are key enzymes in ubiquitination or Ub-like modifications of proteins. We searched for all proteins belonging to the E2 enzyme super-family in seven species (Homo sapiens, Mus musculus, Drosophila melanogaster, Caenorhabditis elegans, Schizosaccharomyces pombe, Saccharomyces cerevisiae, and Arabidopsis thaliana) to identify families and to reconstruct each family's phylogeny. Our phylogenetic analysis of 207 genes led us to define 17 E2 families, with 37 E2 genes, in the human genome. The subdivision of E2 into four classes did not correspond to the phylogenetic tree. The sequence signature HPN (histidine-proline-asparagine), followed by a tryptophan residue at 16 (up to 29) amino acids, was highly conserved. When present, the active cysteine was found 7 to 8 amino acids from the C-terminal end of HPN. The secondary structures were characterized by a canonical alpha/beta fold. Only family 10 deviated from the common organization because the proteins were devoid of enzymatic activity. Family 7 had an insertion between beta strands 1 and 2; families 3, 5 and 14 had an insertion between the active cysteine and the conserved tryptophan. The three-dimensional data of these proteins highlight a strong structural conservation of the core domain. Our analysis shows that the primitive eukaryote ancestor possessed a diversified set of E2 enzymes, thus emphasizing the importance of the Ub pathway. This comprehensive overview of E2 enzymes emphasizes the diversity and evolution of this superfamily and helps clarify the nomenclature and true orthologies. A better understanding of the functions of these enzymes is necessary to decipher several human diseases.
Alignments of E2 protein sequences from different species.